OPIOID IN THE PAIN MANAGEMENT OF ACUTE GOUT ARTHRITIS: FRIEND OR FOE? - Mega Nilam Sari; Florence Pribadi; Eva M. Anigomang; Gede T.W. Suara; Karmila A. Wardani; Kharisma A. Perdana; Lidya Anin; Yasmine P. Fadhilah; Kevin Luke (Jurnal Ilmiah Kesehatan, 2023)
Introduction: Intense and severe pain is the most common symptom of acute gout arthritis (GA) flare. A recent study revealed that opioids are commonly prescribed for acute gout flare. Objective: This review aims to explain current evidence of opioid usage in the management of pain for acute GA flare. Method: The literature search was conducted on PubMed and Google Scholar in June 2022. Relevant articles published in the last 10 years were included. Results: The evidence of opioid use in managing acute gout arthritis flares is scarce. Currently, no guidelines recommend opioids as an initial analgesic choice in managing acute GA flare. Opioids are indicated in the flare with severe kidney dysfunction if only oral corticosteroids and intra-articular corticosteroids are not effective in reducing pain. Conclusion: Opioids should be used as only adjuvant and last choice in selected cases.